PENGEMBANGAN MEDIA POP-UP BOOK MATERI AKTIVITAS KEBUGARAN JASMANI KELAS VI SDN 1 TETEBATU SELATAN - Widi Agus Loreti; Prayogi Dwina Angga; Muhammad Tahir (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2023)
This research aims to develop pop-up book learning media on PJOK learning content material for class IV physical fitness at SDN 1 Tetebatu Selatan. This type of research is the R&D (Research and Development) ADDIE development model with stages of analysis, design, development, implementation and evaluation. Data collection techniques in this research are interviews and questionnaires. Data analysis in this research uses qualitative and quantitative analysis techniques. Qualitative data in this research was obtained from input from validators at the validation stage, input from material experts and media experts. Meanwhile, quantitative is data that describes the results of product development in the form of pop-up book learning media. The pop-up book that has been developed has very feasible criteria with a percentage of 88% based on media validation test results and 89% for material expert validation. Meanwhile, based on the results of product trials that have been developed, the percentage obtained was 87% in small-scale trials, 89% in large-scale trials and 91% based on teacher assessment. This pop-up book on physical fitness activity material is very suitable and very practical in supporting PJOK learning and making it easier for students to understand the physical fitness activity material.